Possibilities of application of natural zeolites in stored wheat grain protection against pest insects - Kljajić Petar; Andrić Goran; Adamović Milan; Pražić-Golić Marijana (Journal on Processing and Energy in Agriculture, 2011)
Natural zeolites are widely used in agriculture, but they also have an insecticidal potential in control of storage insects S. oryzae, R. dominica and T. castaneum. Their efficacy depends on relative air humidity, exposition and powder properties (Natural zeolite - NZ, Modified natural zeolite - MNZ and Fine Granulated Natural zeolite - FGNZ). NZ and MNZ applied at rate 0.25-0.75 g/kg of wheat, at 24ºC and 45±5% r.h., are >90% efficient against S. oryzae and T. castaneum after 21 days of exposition, and against R. dominica 23-73%, when they also have the highest impact on offspring reduction. At a higher r.h. the efficacy against parents (50-55%) and offspring (60±5%) is significantly lower, particularly for MNZ. For treatment of wheat with 1 g/kg NZ and FGNZ, the highest efficacy is after 21 days of exposition (>95% and 79%), and so is the offspring reduction (82 and >90%), which indicates that the use of natural zeolites can provide a successful protection of stored wheat grains from pest insects attack.